The environmental impact of inhalers for asthma: A green challenge and a golden opportunity. Issue 7 (13th December 2021) - Wilkinson, Alex; Woodcock, Ashley
Abstract : The propellants in metered‐dose inhalers (MDIs) are powerful greenhouse gases, which account for approximately 13% of the NHS's carbon footprint related to the delivery of care. Most MDI use is in salbutamol relievers in patients with poorly controlled disease. The UK lags behind Europe in this regard, with greater reliance on salbutamol MDI and correspondingly greater greenhouse gas emissions, roughly treble that of our European neighbours. There has been a broad switch towards MDIs in asthma treatment in the UK over the last 20 years to reduce financial costs, such that the treatment for two‐thirds of asthma patients in the UK is dominated by salbutamol MDI. Strategies that replace overuse of reliever MDIs with regimes emphasising inhaled corticosteroids have the potential to improve asthma control alongside significant reductions in greenhouse gas emissions. Real‐world evidence shows that once‐daily long‐acting combination dry‐powder inhalers (DPIs) can improve compliance and asthma control, and reduce the carbon footprint of care. Similarly, maintenance and reliever therapy (MART), which uses combination reliever and inhaled steroids in one device (usually a DPI), can simplify therapy, improve asthma control and reduce greenhouse gas emissions. Both treatment strategies are popular with patients, most of whom would be willing to change treatment to reduce their carbon footprint. By focussing on patients who are currently using high amounts of salbutamol MDI and prioritising inhaled steroids via DPIs, there are golden opportunities to make asthma care in the UK more effective, safer and greener.